What remains of me : a novel - Gaylin, Alison (William Morrow, an imprint of HarperCollins Publishers, 2016)
"The USA Today bestselling author of the Brenna Spector series returns with her most ambitious book to date, a spellbinding novel of psychological suspense, set in the glamorous, wealthy world of Hollywood-a darkly imaginative and atmospheric tale of revenge and betrayal, presumed guilt and innocence lost, dirty secrets and family ties reminiscent of the bestsellers of Laura Lippman, Gillian Flynn, and Harlan Coben"--